(untitled) (International Conference on Computers in Education, 2016)
With a mobile device in hands, mobile learning serves to provide new learning opm»rtunities to individuals and it fits with many learning environments, both in classroom setting and in informal learning environments. Recently, researchers have an interest in using mobile technologies and simulations to deliver more effective learning experience to students. This presents an exploration of elementary school students’ toward simulation-based mobile learning based on predict-observe-explain (POE) instructional sequence in a physical science lesson of light refraction. A total of ten 4th grade students was recruited to participate in this study. They were administered with 21 items of 5-points Likert scale perception questionnaire regarding six perceptual constructs, i.e. perceived learning (PL), perceived ease of use (PEU), flow (FL), IRrceived usefulness (PL]), enjoyment and perceived satisfaction (PS), after interacting with the approach. The result indicated that there was some high degree of positive perceptions toward the approach, and the highest percentage of their perceptions were PU, E, PS, FL, PL, and PEU, respectively. Based on the finding, the simulation-based mobile learning based on POE approach will be redesigned for enhancing students’ learning performance in the next study.